The audit quality factors’ impact on accrual earnings management-evidence from the UK public companies' industrial and commercial sectors - WANG, Jiachen (2020)
This paper studies the impact of audit quality factors on accrual earnings management which breeds agency problems. The research object is the auditing competency and audit independence of the industrial and commercial sectors in British public companies. This thesis takes public secondary resource with quantitative research methods and using three empirical models separately to study the impact of the audit firm's reputation, audit company tenure, non-audit service fees and audit fees on accrual earnings management in the overall, industrial and commercial sector. This article not only studies the impact of the above primary elements on earnings management, but also because of the gaps in the research on this topic in the UK's public company, this article continues to study the relationship between independent variable's interaction and earnings management, and the nonlinearity relationship between audit fees and earnings management. This paper finds that whether auditing companies belong to the Big Four, the audit company's tenure and non-audit service fees have a negative correlation with accrued earnings management. In contrast, the interaction between audit tenure and non-audit services has a positive correlation with earnings management. The industrial sector is more sensitive to all correlation than the commercial sector. Moreover, the audit fee and earnings management present a "U"-shaped relationship, that is, negative correlation first, then positive correlation and the critical points between sectors are similar. The main contribution of this article is to provide British public companies with an analysis structure of the impact of audit quality proxies on accrual earnings management.